Advances in computational morphodynamics using the International River Interface Cooperative (iRIC) software. Issue 1 (17th July 2019) - Shimizu, Yasuyuki; Nelson, Jonathan; Arnez Ferrel, Kattia; Asahi, Kazutake; Giri, Sanjay; Inoue, Takuya; Iwasaki, Toshiki; Jang, Chang‐Lae; Kang, Taeun; Kimura, Ichiro; Kyuka, Tomoko; Mishra, Jagriti; et al.
Abstract: Results from computational morphodynamics modeling of coupled flow–bed–sediment systems are described for 10 applications as a review of recent advances in the field. Each of these applications is drawn from solvers included in the public‐domain International River Interface Cooperative (iRIC) software package. For mesoscale river features such as bars, predictions of alternate and higher mode river bars are shown for flows with equilibrium sediment supply and for a single case of oversupplied sediment. For microscale bed features such as bedforms, computational results are shown for the development and evolution of two‐dimensional bedforms using a simple closure‐based two‐dimensional model, for two‐ and three‐dimensional ripples and dunes using a three‐dimensional large‐eddy simulation flow model coupled to a physics‐based particle transport model, and for the development of bed streaks using a three‐dimensional unsteady Reynolds‐averaged Navier–Stokes solver with a simple sediment‐transport treatment. Finally, macroscale or channel evolution treatments are used to examine the temporal development of meandering channels, a failure model for cantilevered banks, the effect of bank vegetation on channel width, the development of channel networks in tidal systems, and the evolution of bedrock channels. In all examples, computational morphodynamics results from iRIC solvers compare well to observations of natural bed morphology. For each of the three scales investigated here, brief suggestions for future work and potential research directions are offered. © 2019 The Authors Earth Surface Processes and Landforms Published by John Wiley & Sons Ltd Abstract : Results from computational morphodynamics modeling of coupled flow‐bed‐sediment systems are described for 10 applications as a review of recent advances in the field. Each of these applications is drawn from solvers included in the public‐domain International River Interface Cooperative (iRIC) software package. In all examples, computational morphodynamics results from iRIC solvers compare well to observations of natural bed morphology. For each of the morphodynamics problems investigated here, brief suggestions for future work and potential research directions are offered.